Propuesta para mejorar la calidad del agua de consumo humano de la Junta de Agua de Cuicocha del Cantón Cotacachi - Yamá Potosí, Jonathan Javier (2023)
This research is based on the need of the community of Cuicocha that through the organization UNIÓN DE ORGANIZACIONES CAMPESINAS INDÍGENAS DE COTACACHI (UNORCAC) requests through the office to monitor their water sources for human consumption, Therefore, the research topic 'PROPOSAL TO IMPROVE THE QUALITY OF WATER FOR HUMAN CONSUMPTION OF THE CUICOCHA WATER BOARD OF THE CANTON COTACACHI' was proposed in order to evaluate the quality of water for human consumption and make a proposal for improvement. The procedures used in the water analysis start with the collection of samples from different sources, complying with the protocols for monitoring drinking water for physical-chemical and microbiological analysis such as: electrical conductivity, pH, turbidity, residual chlorine, using on-site monitoring equipment, and total solids, total hardness, calcium, magnesium, nitrites, nitrates, COD, sulfates, and total coliforms in the laboratory. Once the physical-chemical and biological characteristics of the water were determined we proceeded to compare them with the current standard TULSMA book VI annex 1, of the official registry N°387, ministerial agreement 097A. 2015, concluding that the values of the parameters analyzed comply with current regulations. As a final result, a proposal for monitoring, evaluation and follow-up of water quality was obtained. This research work will facilitate having periodic data on water consumption, which will allow establishing possible treatments for the improvement and proper use of this resource, ensuring the welfare of the people of the community and its future generations.